Efficient regio- and stereoselective access to novel fluorinated β-aminocyclohexanecarboxylates - Kiss, Loránd; Nonn, Melinda; Sillanpää, Reijo; Fustero, Santos; Fülöp, Ferenc (Beilstein Journal of Organic Chemistry, 2013)
A regio- and stereoselective method has been developed for the synthesis of novel fluorinated 2-aminocyclohexanecarboxylic acid derivatives with the fluorine attached to position 4 of the ring. The synthesis starts from either cis- or trans-β-aminocyclohex-4-enecarboxylic acids and involves regio- and stereoselective transformation of the ring C–C double bond through iodooxazine formation and hydroxylation, followed by hydroxy–fluorine or oxo–fluorine exchange.
Keywords: amino acids; epoxidation; fluorination; hydroxylation; stereoselective reaction